Structure degradation and strength changes of sintered calcium phosphate bone scaffolds with different phase structures during simulated biodegradation in vitro - Stastny, Premysl; Sedlacek, Radek; Suchy, Tomas; Lukasova, Vera; Rampichova, Michala; Trunec, Martin (Materials science & engineering. C, Materials for biological applications, 2019)
The structure degradation and strength changes of calcium phosphate scaffolds after long-term exposure to an acidic environment simulating the osteoclastic activity were determined and compared. Sintered calcium phosphate scaffolds with different phase structures were prepared with a similar cellular pore structure and an open porosity of over 80%. Due to microstructural features the biphasic calcium phosphate (BCP) scaffolds had a higher compressive strength of 1.7 MPa compared with the hydroxyapatite (HA) and β-tricalcium phosphate (TCP) scaffolds, which exhibited a similar strength of 1.2 MPa. After exposure to an acidic buffer solution of pH = 5.5, the strength of the HA scaffolds did not change over 14 days. On the other hand, the strength of the TCP scaffolds decreased steeply in the first 2 days and reached a negligible value of 0.09 MPa after 14 days. The strength of the BCP scaffolds showed a steady decrease with a reasonable value of 0.5 MPa after 14 days. The mass loss, phase composition and microstructural changes of the scaffolds during degradation in the acidic environment were investigated and a mechanism of scaffold degradation was proposed. The BCP scaffold showed the best cell response in the in vitro tests. The BCP scaffold structure with the highly soluble phase (α-TCP) embedded in a less soluble matrix (β-TCP/HA) exhibited a controllable degradation with a suitable strength stability and with beneficial biological behavior it represented the preferred calcium phosphate structure for a resorbable bone scaffold.
Keywords: pevnost v tlaku; tkáňové podpůrné struktury; mezenchymální kmenové buňky; Hydrogen-Ion Concentration; fosforečnany vápenaté; Ceramics; poréznost; buněčná adheze; Calcium Phosphates; kosti a kostní tkáň; DNA; lidé; Cell Adhesion; Porosity; Mesenchymal Stem Cells; keramika; Compressive Strength; Bone and Bones; koncentrace vodíkových iontů; Tissue Scaffolds; Humans